Seasonal Variations in Fish Diversity and Community Structure in Urban Freshwater Reservoirs: A Case Study of Bhadrakali and Waddepally in Warangal, Telangana - Jarupala, L. S.; Ganesh, G.; Subhashini, P.; Suhashini, G.; Raju, P. (International Journal of Bio-resource and Stress Management, 2025)
The present study was conducted over a two-year period from (June, 2022 to May, 2024) at Warangal District, Telangana, India to investigate the seasonal diversity of freshwater fishes in two urban reservoirs Bhadrakali and Waddepally located in Warangal district, Telangana, India. Despite the region's prominence in inland fish production, systematic documentation of its ichthyofaunal diversity remains limited. This study aimed to address this gap by examining fish species composition in relation to seasonal variations and physico-chemical water quality parameters. Monthly sampling was conducted with the assistance of local fishermen using traditional seine nets. Collected fish specimens were preserved using standard formalin-based techniques and identified based on morphological features, including body shape, fin structure, coloration and distinctive surface markings. Local nomenclature and ecological observations were also recorded to support species identification and understand habitat-specific diversity. Seasonal changes significantly influenced the presence and abundance of different species, highlighting the dynamic nature of these urban aquatic ecosystems. The results underscored the reservoirs roles not only in supporting regional fish production but also in sustaining aquatic biodiversity. This study provided essential baseline data for future ecological assessments, conservation planning and sustainable fisheries development in the region. Furthermore, it emphasized the importance of protecting urban freshwater bodies, which were increasingly threatened by pollution, encroachment and unregulated resource exploitation. The findings contributed to better understanding and management of aquatic biodiversity in urban settings and could guide policy interventions for long-term ecological sustainability.